2018
DOI: 10.1002/da.22866
|View full text |Cite
|
Sign up to set email alerts
|

Structural imaging biomarkers for bipolar disorder: Meta‐analyses of whole‐brain voxel‐based morphometry studies

Abstract: Background: Bipolar disorder (BD) is a common and destructive psychiatric illness worldwide.Although it is known that BD is associated with morphological abnormalities of the brain, the regions implicated in BD remain unclear. Therefore, we aimed to update current knowledge on potential structural imaging biomarkers of BD. Methods: Studies published up to January 31, 2018, were identified by a comprehensive literature search of PubMed, EBSCO, and BrainMap voxel-based morphometry (VBM) database. Wholebrain VBM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 100 publications
6
26
0
5
Order By: Relevance
“…There have been many proofs that show the limbic system involving emotional processing, memory, and executive functioning, as well as its decreases of gray matter in patients with bipolar disorder [19,23,[67][68][69][70][71]. Besides, we identi ed decreased gray matter volume in the superior temporal gyrus and inferior temporal gyrus; this nding was consistent with most previous structural MRI studies in BPD [26,[72][73][74].Temporal lobe is the brain region related to hearing and vision and thought to play a crucial role in emotional processing, working memory, and social cognition. [75][76].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There have been many proofs that show the limbic system involving emotional processing, memory, and executive functioning, as well as its decreases of gray matter in patients with bipolar disorder [19,23,[67][68][69][70][71]. Besides, we identi ed decreased gray matter volume in the superior temporal gyrus and inferior temporal gyrus; this nding was consistent with most previous structural MRI studies in BPD [26,[72][73][74].Temporal lobe is the brain region related to hearing and vision and thought to play a crucial role in emotional processing, working memory, and social cognition. [75][76].…”
Section: Discussionsupporting
confidence: 90%
“…They found that BPD patients had a decreased superior temporal gyrus gray matter volume than BPD [74]. Two previous meta-analyses also con rmed decreased gray matter volume in the superior temporal gyrus only in BPD I patients [73,80]. It can be speculated that de cit in superior temporal gyrus is unique to BPD type I.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Compelling evidence indicated that prefrontal cortex (PFC) is a key region in the pathophysiology of BD . Furthermore, behavioural and imaging studies supported the proposition that manic episodes are strongly associated with alterations in PFC structure …”
Section: Introductionmentioning
confidence: 96%
“…Not only have several meta-analyses of different diseases shown that such reductions are common (Fornito et al, 2009;Bora et al, 2010Bora et al, , 2011Bora et al, , 2012aFusar-Poli et al, 2011;Hallahan et al, 2011;Linkersdörfer et al, 2012;Du et al, 2012;Li et al, 2014Li et al, , 2018Stoodley, 2014;Cauda et al, 2014;Foster et al, 2015;Lin et al, 2016;Wise et al, 2017;Wu et al, 2018), and other work suggests that anatomically distributed yet coordinated GM reductions are tied to the underlying connectivity between regions (Seeley et al, 2009;Raj et al, 2012;Zhou et al, 2012;Crossley et al, 2014;Iturria-Medina et al, 2014;Zeighami et al, 2015, Cauda et al, 2018aYau et al, 2018;Zheng et al, 2019). In contrast, GM increases are less commonly considered in clinical neuroimaging studies (Cauda et al, 2011(Cauda et al, , 2017(Cauda et al, , 2018bTatu et al, 2018, Cauda et al, 2019bDing et al, 2019;Lu et al, 2019), potentially because they might be a rarer consequence of disease and because they can be difficult to explain in the context of pathology. Indeed, while a morphometric decrease can be easily interpreted as a sign of neurodegeneration or neurodevelopmental hyperpruning, the interpretation of a disorder-related GM increase is less clear.…”
Section: Introductionmentioning
confidence: 99%